PELATIHAN SENI KALIGRAFI DI MI AL HIKMAH TAMBUN SELATAN - Lulu Isnaini; Aulia Ayu Rohayah; Siti Asiah (Al-Ihsan: Journal of Community Development in Islamic Studies, 2022)
This program is held to develop the talents of every student at Madrasah Ibtidaiyah Al-Hikmah. By carrying out 3 activities in this Arabic (Calligraphy) writing training program, which uses the face-to-face 2-meeting training method, and the training method via Whatsapp group. During the face-to-face training, 2 techniques were used, the first was the technique of writing with 1 tilted pencil, and the second was the technique of writing with 2 pencils tied together. Meanwhile, the training was via whatsapp group, with material videos and tutorials on how to write calligraphy with 2 pencils that were tied and colored. The target participants in these 2 activities are different, during the face-to-face training the target is class 5 MI, while the training via whatsapp group has a mix of participants from class 5 Madrasah Ibtidaiyah around South Tambun Demon